Assessment of mismatch repair deficiency in ovarian cancer. Issue 10 (11th September 2020) - Crosbie, Emma J; Ryan, Neil A J; McVey, Rhona J; Lalloo, Fiona; Bowers, Naomi; Green, Kate; Woodward, Emma R; Clancy, Tara; Bolton, James; Wallace, Andrew J; McMahon, Raymond F; Evans, D Gareth
Abstract : Background: Hereditary causes of ovarian cancer include Lynch syndrome, which is due to inherited pathogenic variants affecting one of the four mismatch repair genes involved in DNA repair. The aim of this study was to evaluate tumour mismatch repair deficiency and prevalence of Lynch syndrome in high-risk women referred to the Manchester Centre for Genomic Medicine with ovarian cancer over the past 20 years. Methods: Women with ovarian cancer diagnosed before the age of 35 years and/or with a suggestive personal or family history of Lynch syndrome cancers underwent tumour testing with immunohistochemistry for mismatch repair deficiency and, where indicated, MLH1 promoter methylation testing followed by constitutional testing for Lynch syndrome. Results: In total, 261 ovarian cancers were tested and 27 (10.3%; 95% CI 6.9% to 14.7%) showed mismatch repair deficiency by immunohistochemistry. Three of 7 with MLH1 loss showed MLH1 promoter hypermethylation, and 18 of the remaining 24 underwent constitutional testing for Lynch syndrome. A further 15 women with mismatch repair proficient tumours underwent constitutional testing because of a strong family history of Lynch syndrome cancers. Pathogenic variants were identified in 9/33 (27%) women who underwent constitutional testing, aged 33–59 years (median 48 years), including one whose tumour was mismatch repair proficient. Most Lynch syndrome tumours were of endometrioid histological subtype. Conclusions: Tumour mismatch repair deficiency identified by immunohistochemistry is a useful prescreen for constitutional testing in women with ovarian cancer with personal or family histories suggestive of Lynch syndrome.